Ǝrəxša’s self-sacrifice: Tradition or Innovation? - PANAINO, Antonio (Historia i Świat, 2021)
The reconstruction the heroic cycle of Ǝrəxša is one of the main targets of our investigations. The present cycle cannot be studied just as an isolated fragment of an archaic epos, but that it must be framed into a larger theme, that of the bow and the arrow, which among the Indo-European tribes of the East, mostly Indo-Iranians and Hittites, assumed a remarkable importance.